Youth Perception of Self-Harm in Serialised Audiovisual Fiction: A Quantitative Analysis - Magro-Vela, Silvia; Moraleda-Esteban, Raquel; Sánchez-López, Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
Non-suicidal self-injury is a growing issue among young people, but its portrayal in fiction is recent. This study explores university students’ perceptions of audiovisual sequences showing explicit self-injury. The 216 surveys reveal strong awareness of self-injury and a more realistic depiction, often focusing on cuts in private. Girls identify the scenes more, while boys see more romanticization. Most participants believe viewing such content could negatively affect young people with self-injury, although they agree it helps raise awareness of the issue, which is underrepresented in current popular culture.